Karl Sax’s Letters About the „Bosnian Turks“ and the Turkish Language in Bosnia (19th Century) - Čaušević, Ekrem (Prilozi za orijentalnu filologiju, 2017)
In the supplement Karl Sax's Letters about .Bosnian Turks. and the Turkish Language in Bosnia (19th century), readers have been presented with two letters that Karl Sax, an officer of the Prussian Embassy in Sarajevo, sent to a professor Wickerhauser in 1862 and 1863. With an inadequate amount of direct evidence about the linguistic situation in Bosnia in the mid-19th century, Sax.s letters are quite important as they contain some new information . although insufficient . about the so-called Bosnian Turkish language (more precisely: dialect), first of all about accent and congruence of subject and object. This paper has been dedicated to the analysis of the information and observations offered, which have not been used to date although they came from the pen of an obviously educated philologist.